Change in Vegetation Cover of Dampa Tiger Reserve, Mizoram, North East India: A Serious Threat to Tiger Population - K. Sarma1, H. Suchitra Devi1*, Hmingthangpuii2, K. (Journal of Experimental Sciences, 2011)
<span style="font-size: 10pt; font-family: ";Arial Narrow";,";sans-serif";; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-family: 'Times New Roman';">Change in vegetation cover drastically alters the status of a habitat. A dramatic change in vegetation cover of Dampa Tiger Reserve was observed during the last 27 years. There was a prominent increase in built up (590%), bamboo forest (192.89%) and scrub (74.67%) areas. These increases are simultaneously accompanied by decrease in cover area of evergreen/semi evergreen closed forests from 152.47 sq km in 1978 to 95.27 sq km in 2005. Meanwhile the population of tiger as per tiger census during this period in the reserve was only four to five. As there is hardly any report of poaching, we assume that this constant population instead of growth may largely be due to change in vegetation cover. The root cause of this vegetation change was due to practice of shifting cultivation by villagers in and around the reserve and people reaching from far away places. This in totality resulted in shrinkage of tiger habitat. Though the reserve based on IUCN framework, scored 121 score grading among all the tiger reserves in India and placed in category, ‘Good’, the changing pattern of vegetation is alarming and pose a serious threat to the present tiger population within the reserve.